Effect of length of albendazole treatment against Trichuris trichiura infection - Aridamuriany D Lubis; Syahril Pasaribu; Muhammad Ali; Munar Lubis (Paediatrica Indonesiana, 2013)
Background Trichuris trichiura is one of the most common soil-transmitted helminth that infects school-aged children. A single dose of albendazole has been shown to have wide variations in cure and egg reduction rates. Some studies have suggested that repeated doses of albendazole might increase its effectiveness.Objective To compare the anti-trichuriasis effect of 400 mg albendazole taken daily for five consecutive days vs. seven consecutive days.Methods A randomized open clinical trial was conducted from August to September 2009 on elementary school children at Jaring Halus in the North Sumatera Province. Stool specimens were collected before treatment and on days 7, 14, 21, and 28 after initiation of treatment, and examined by the Kato Katz method. Subjects were randomized into two groups. Group I received 400 mg albendazole daily for five consecutive days and Group II received 400 mg albendazole daily for seven consecutive days. Cure rates and egg reduction rates were compared using Chi-square and T-tests, respectively.Results One hundred twenty-one children were enrolled, consisted of 61 children in Group I and 60 in Group II. For the first week after treatment ended, the cure rates in Group II was higher (86.7%) than in the Group I (39.3%) (P=0.001), as well as in the second week after treatment ended (88.3% vs 68.9%, P=0.017). However, after 3rd and 4th weeks, the cure rates were no longer significantly different. Egg reduction rate was also statistically higher in the Group II [20.3 (SD 23.77) %] compared to Group I [6.6 (SD 11.30) %].Conclusions Albendazole for seven consecutive days is more effective in curing Trichuris trichiura infection in the 1st and 2nd weeks after treatment compared to that of five consecutive days, as well as in egg reduction rate, but the length of treatment does not influence the cure rate after the 3rd and 4th weeks.